2022
DOI: 10.1113/jp283299
|View full text |Cite
|
Sign up to set email alerts
|

Novel identification and modulation of the mechanosensitive Piezo1 channel in human myometrium

Abstract: Approximately 10% of US births deliver preterm before 37 weeks of completed gestation. Premature infants are at risk for life‐long debilitating morbidities and death, and spontaneous preterm labour explains 50% of preterm births. In all cases existing treatments are ineffective, and none are FDA approved. The mechanisms that initiate preterm labour are not well understood but may result from dysfunctional regulation of quiescence mechanisms. Human pregnancy is accompanied by large increases in blood flow, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…All pregnant human myometrial tissue collection adhered to the regulations set by the Declaration of Helsinki and approved by the Institutional Review Board at the University of Nevada Biomedical Review Committee for the protection of human subjects. Women with a singleton pregnancy that were having a Cesarean section (C/S) gave their verbal and written consent to have a piece of uterine smooth muscle tissue excised as described [ 14 , 31 ]. We collect all de-identified data on the treatments and pregnancy course prior to C/S as well as the presence and degree, or absence of infection, mother’s BMI, sex of the infant, smoking status of the mother and social indicators including socioeconomic status, prenatal care, and maternal education when available.…”
Section: Methodsmentioning
confidence: 99%
“…All pregnant human myometrial tissue collection adhered to the regulations set by the Declaration of Helsinki and approved by the Institutional Review Board at the University of Nevada Biomedical Review Committee for the protection of human subjects. Women with a singleton pregnancy that were having a Cesarean section (C/S) gave their verbal and written consent to have a piece of uterine smooth muscle tissue excised as described [ 14 , 31 ]. We collect all de-identified data on the treatments and pregnancy course prior to C/S as well as the presence and degree, or absence of infection, mother’s BMI, sex of the infant, smoking status of the mother and social indicators including socioeconomic status, prenatal care, and maternal education when available.…”
Section: Methodsmentioning
confidence: 99%
“…In our Special Issue, Barnett et al. (2023) share their discovery that Piezo1 has key functions in a very different tissue, namely human myometrium. There, it is modulated by protein kinase A/AKT/endothelial nitric oxide synthase‐mediated paracrine signalling between the microvascular endothelium and uterine smooth muscle, thereby ensuring quiescence during gestation.…”
mentioning
confidence: 99%
“…It is noteworthy that less Piezo1 is expressed in myometrium from women experiencing preterm labour. These studies therefore reveal potential targets for the development of therapies to mitigate this condition and its extenuating consequences (Barnett et al., 2023). To complement these insights, an accompanying Journal Club article (Majhi et al., 2023) concisely and thoroughly considers the implications of the study by Barnett et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanosensitive channels present in the myometrium likely sense this mechanical stretch and their activation triggers a mechanism that sustains quiescence. In a recent study published in The Journal of Physiology, Barnett et al set out to characterize the expression pattern and (patho)physiological role of the mechanosensitive channel PIEZO1 in quiescence and PTL mechanisms of the human myometrium (Barnett et al, 2022). They found that PIEZO1 levels are comparable in the myometrium of non-pregnant women and women at term or preterm but without initiation of labour.…”
mentioning
confidence: 99%